2022
DOI: 10.1186/s12905-022-01784-0
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the use of long term and permanent contraceptive methods: a Facebook-focused cross-sectional study

Abstract: Introduction In the Muslim world, the use and acceptance of long-term and permanent contraceptives were limited. Our aim was to investigate those limiting factors so we can help making these methods widely available and acceptable to the society. Methods and data analysis There were 1365 women from Facebook groups in the period 08/10/2020–8/11/2020. Participants were married women, living in Jordan. This was a cross-sectional study. Statistical Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
1
1
1
Order By: Relevance
“…Most of the females in this study learned about family planning methods from their parents, relatives, and friends (38.75%) and then from healthcare providers (31.5%). This finding is similar to that of other earlier Saudi studies [12,17,27,28], and this result may be due to Saudi cultural norms and a lack of a school curriculum that teaches students about reproductive health issues, including birth spacing and its benefits for females and child health. Based on this important discovery, healthcare professionals should be given more authority and instructions to inform females about family planning options.…”
Section: Discussionsupporting
confidence: 90%
“…Most of the females in this study learned about family planning methods from their parents, relatives, and friends (38.75%) and then from healthcare providers (31.5%). This finding is similar to that of other earlier Saudi studies [12,17,27,28], and this result may be due to Saudi cultural norms and a lack of a school curriculum that teaches students about reproductive health issues, including birth spacing and its benefits for females and child health. Based on this important discovery, healthcare professionals should be given more authority and instructions to inform females about family planning options.…”
Section: Discussionsupporting
confidence: 90%
“…Firstly, the age of women (X1) does not significantly impact their decision, which contrasts with research by Darsono et al (2020) and Gayatri (2022), who found that age, particularly among women over 35, significantly influences the choice of LARC. Similarly, the education level of women (X2) shows no significant effect on this choice, diverging from findings by Al-Husban et al (2022) and Azis et al (2021).…”
Section: Determinants Of Choosing Larc and Non-larc Among Family Plan...contrasting
confidence: 57%
“…However, studies reported that women in LMICs faced multifaceted barriers to permanent contraception (2). The myths, procedure irreversibility, and religious beliefs increase females' fear of deciding to use permanent contraception (3). Unsupportive husbands toward their decisions also reportedly hinder females from using this method (4).…”
Section: Introductionmentioning
confidence: 99%